2008
DOI: 10.2143/anes.45.0.2033167
|View full text |Cite
|
Sign up to set email alerts
|

Comments on the Early/Middle Iron Age Chronology of Lake Van Basin

Abstract: In the Van Lake basin, or in Northeast Anatolia in general, Early Iron Age denotes pre-Urartian times. Although the beginning of this age is rather obscure, it is generally accepted that it came to an end with the establishment of the Urartian Kingdom in the middle of the ninth century BC. Following the focus on a number of large, well-planned Urartian sites over the last hundred years or so, there has been a shift in the last twenty years to small, rural settlements and necropoleis, like Dilkaya, Karagündüz a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The existence of both inhumation and cremation in the same grave and only the last body kept its original position creating a pile of older skeletons at the back of the grave are also characteristics of the Urartian graves 25 . 23 It suggested that, cemeteries of Yoncatepe, Karagündüz and Dilkaya must be belong to the Urartian period based on two bronze fibulae found in the Yoncatepe grave M3, an arrowhead from the grave M6 (see Konyar 2005;Köroğlu/Konyar 2005;Köroğlu/Konyar 2008). Published material of Yoncatepe contains a large number of pinkish buff ware and the lesser number of red slipped ware found just like in Karagündüz and Dilkaya which is typical EIA pottery of the region as pointed out by Sevin (2014: 359-360).…”
Section: Discussion-summarymentioning
confidence: 99%
“…The existence of both inhumation and cremation in the same grave and only the last body kept its original position creating a pile of older skeletons at the back of the grave are also characteristics of the Urartian graves 25 . 23 It suggested that, cemeteries of Yoncatepe, Karagündüz and Dilkaya must be belong to the Urartian period based on two bronze fibulae found in the Yoncatepe grave M3, an arrowhead from the grave M6 (see Konyar 2005;Köroğlu/Konyar 2005;Köroğlu/Konyar 2008). Published material of Yoncatepe contains a large number of pinkish buff ware and the lesser number of red slipped ware found just like in Karagündüz and Dilkaya which is typical EIA pottery of the region as pointed out by Sevin (2014: 359-360).…”
Section: Discussion-summarymentioning
confidence: 99%
“…The high proportion of iron relative to bronze in these tombs has led some to suggest an earlier adoption in eastern Anatolia relative to the South Caucasus (Çevik, 2008:10). However, the chronology of these sites is contentious, as some have dated them to the Urartian period (c. 900-600 BC) (Köruoğlu and Konyar, 2008). In present day Armenia and Eastern Georgia, iron artifacts are reported from late 2nd millennium graves (Abramishvili, 1957;Khanzadian, 1995:67), but radiocarbon dates are lacking.…”
Section: Iron Innovation In the Caucasusmentioning
confidence: 99%
“…In eastern Anatolia, graves at Karagündüz are notable for the preponderance of iron artifacts over those made from copper alloys. While radiocarbon assays provide a 12th-century BC date for some of the bones, the ceramic chronology has been questioned by some scholars, who see similarities with pottery found at later sites (Çevik 2008;Köruoğlu 2003;Köruoğlu and Konyar 2008;Sagona and Zimansky 2009, p. 319;Sevin 2003, p. 195). McConchie (2004, pp.…”
Section: Anatoliamentioning
confidence: 99%